2016
DOI: 10.1503/cmaj.1150076
|View full text |Cite
|
Sign up to set email alerts
|

Public health benefits from legalizing cannabis: both sides of the coin

Abstract: Go to cmaj.ca for the full-text version of this letter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…However, in countries where cannabis is legal, it has been observed that the majority of users prefer more potent extracts with a higher content of delta‐9‐tetrahydrocannabinol (THC), which is the chemical compound responsible for the psychoactive (and slightly hallucinogenic) drug effects [43]. In addition, in the areas where cannabis legalization policies were implemented, there was a significant decrease in the population of opioid users, although there was no significant differentiation in the population of cannabis users as well as a rather upward trend in the population of users of illegal CNS stimulants [41,42]. In areas where cannabis use is legalized, there is insufficient evidence to support or refute a statistical correlation between cannabis use and all‐cause mortality or occupational accidents/injuries [20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in countries where cannabis is legal, it has been observed that the majority of users prefer more potent extracts with a higher content of delta‐9‐tetrahydrocannabinol (THC), which is the chemical compound responsible for the psychoactive (and slightly hallucinogenic) drug effects [43]. In addition, in the areas where cannabis legalization policies were implemented, there was a significant decrease in the population of opioid users, although there was no significant differentiation in the population of cannabis users as well as a rather upward trend in the population of users of illegal CNS stimulants [41,42]. In areas where cannabis use is legalized, there is insufficient evidence to support or refute a statistical correlation between cannabis use and all‐cause mortality or occupational accidents/injuries [20].…”
Section: Discussionmentioning
confidence: 99%
“…The reason for legalization may vary from country to country, as to whether it is allowed for industrial, medical, or recreational usage (or all of the abovementioned). At a social level, cannabis legalization has been associated with reduced rates regarding drug-related crimes in the areas where it has been applied and, consequently, reduced death figures and lower medical costs deriving from this population portion [41,42]. At an economic level, the common perception expressed by the proponents of cannabis legalization revolves around the concept of mutual benefit on both sides.…”
Section: Illicit Substance Users Accused Of Drug Law Offenses (Sample #2)mentioning
confidence: 99%
See 1 more Smart Citation
“…The urgency is justified by the rapidly increasing approvals of many states and countries to allow medicinal and recreational use of marijuana and its individual components. While the legalization and decriminalization of the use of marijuana and associated compounds benefit society in many respects (Mitchell, 2016), full understanding of the potential risks is lagging. Nonetheless, based on the information that is available, use of marijuana or associated compounds is not recommended before, during, and after pregnancy even through adolescence.…”
Section: Introductionmentioning
confidence: 99%
“…When covered, claims are typically subjective to restrictions on medical conditions for which medical cannabis can be used for along with yearly monetary caps and at times, administrative procedures are required to prove all other pharmaceutical options have been attempted. 8 …”
mentioning
confidence: 99%